Identification of critical causes of construction accidents in China using a model based on system thinking and case analysis. (January 2020) - Zhang, Wei; Zhu, Shuangna; Zhang, Xiao; Zhao, Tingsheng
Graphical abstract: Highlights: Construction accident causes were considered as a system and decomposed into six subsystems, 16 factors and 39 sub-factors in a system thinking way. The 39 sub-factors were classified to rigorous, critical and ordinary, based on a grey relational analysis of the causes of 571 real accident cases. The causes of a serious collapse accident in Fengcheng Power Plant Project was analyzed as a case study. Abstract: Hundreds of accidents occur each year in the construction industry and result in large numbers of injuries, deaths, and loss of property. Although construction safety management aims for zero accidents, this is difficult to achieve because of multiple factors influencing the occurrence of accidents. To clarify the framework for construction accident prevention, this study uses accident causation theory and the system thinking method to build a construction accident causation system (CACS) model and identify critical accident causes. Construction accident causes are considered as a whole system and then decomposed into 6 subsystems, 16 factors, and 39 subfactors. The investigation reports of 571 construction accidents in China are collected, and a grey relational analysis (GRA) of accident causes is conducted. Based on these results, the 39 subfactors are classified into 3 severity levels: critical, important, and ordinary. A case study is then conducted with respect to the particularly serious collapse accident that occurred during the Fengcheng Power Plant project. The occurrence process, major reasons for the accident, and related management defects are investigated and causes are identified. The results about accident cause identification of the case study are found to be consistent with the GRA of 571 accidents. Finally, recommendations for construction safety management and accident prevention in practice are proposed.